The Review of Computer Literacy Standards in Virtual Education - mohsen keshararz; mehran farajollahi; bahman zandi (Zanjan University of Medical Sciences and Health Services, 2017)
Background and objective: The main purpose of this article was a review of students' computer literacy level who were studying through distance education at University of Tehran, Faculty of Management. Materials and Methods: This study was a descriptive-survey research in which 171 students were selected. Research instrument was a questionnaire of computer literacy based on standards of ICDL. The reliability index for the total test was 0.70. Result: Components of Information Technology; Windows; Word; PowerPoint; Excel and Access were relatively at a desirable level. Component of Internet was the only one at a desirable level. Also, general computer literacy skills were relatively at a desirable level. Conclusion: One of the most important technical skills in the system of distance education is computer literacy skill. Having this skill will contribute to access information and knowledge. Therefore, planning to teach computer literacy skills is essential in medical and non-medical sciences universities.